2023
DOI: 10.3390/molecules28114452
|View full text |Cite
|
Sign up to set email alerts
|

Riok1, A Novel Potential Target in MSI-High p53 Mutant Colorectal Cancer Cells

Abstract: The vulnerabilities of cancer cells constitute a promising strategy for drug therapeutics. This paper integrates proteomics, bioinformatics, and cell genotype together with in vitro cell proliferation assays to identify key biological processes and potential novel kinases that could account, at least in part, for the clinical differences observed in colorectal cancer (CRC) patients. This study started by focusing on CRC cell lines stratified by their microsatellite (MS) state and p53 genotype. It shows that ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…However, this compound might also target other kinases, including RioK3 [65], but experimental evidence in this regard remains lacking. Recently, Nintedanib, a tyrosine kinase inhibitor approved for use in idiopathic pulmonary fibrosis, also targeted RioK1 in colorectal cancer cells [66]. More desirable precision approaches could involve developing ligands that target the post-translational modifications of RioK1 (p-S407, p-T410, met-K411), which determine its activity and stability.…”
Section: Riok1 As a Broad-acting Anti-cancer Drug Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this compound might also target other kinases, including RioK3 [65], but experimental evidence in this regard remains lacking. Recently, Nintedanib, a tyrosine kinase inhibitor approved for use in idiopathic pulmonary fibrosis, also targeted RioK1 in colorectal cancer cells [66]. More desirable precision approaches could involve developing ligands that target the post-translational modifications of RioK1 (p-S407, p-T410, met-K411), which determine its activity and stability.…”
Section: Riok1 As a Broad-acting Anti-cancer Drug Targetmentioning
confidence: 99%
“…These could be combined with compounds that disrupt the MDM2-p53 interaction [56] or that target RioK1 to enhance the stability of re-activated mutant p53, similar to inhibiting RioK1 in cancer cells expressing wild-type p53 [2]. Recent reports revealed that genetically downregulating or drug (Nintedanib) treating RioK1 abrogated the growth and proliferation of malignancies expressing gain-of-function mutant p53 [15,66]. However, considering that neither p53 stability nor activity was probed, and given that RioK1 mediates myriad roles in cells, while Nintedanib does not target RioK1 exclusively, it cannot be excluded that secondary activities were aspecifically affected in both studies, causing the observed cytotoxicities.…”
Section: Riok1 As a Broad-acting Anti-cancer Drug Targetmentioning
confidence: 99%